Escalation of Anesthesia In Vitrectomy for Chronic Kidney Disease Patients: From Peribulbar Block to General Anesthesia - Ida Bagus Indrayoga Permana; I Made Gede Widnyana (Universitas Malahayati, 2026)
ABSTRACT Patients with Stage V Chronic Kidney Disease (CKD) face a significantly higher risk of ocular pathologies, notably Tractional Retinal Detachment (TRD) resulting from proliferative diabetic retinopathy. Anesthetic management for these patients is complex due to impaired drug clearance, cardiovascular comorbidities (CHF, HHD), and the necessity for absolute ocular immobility during vitreoretinal surgery. Regional anesthesia is typically preferred to minimize systemic complications, though technical escalation may be required. A 43-year-old male with Stage V CKD on regular hemodialysis, CHF (FC II), and Type II Diabetes Mellitus was scheduled for a left eye vitrectomy. An initial peribulbar block (8 mL Lidocaine 2% and Bupivacaine 0.5%) resulted in partial akinesia (score 4/8). A rescue Sub-Tenon block successfully achieved total akinesia (score 0/8). However, intraoperative agitation necessitated propofol sedation, which led to oversedation and airway obstruction. Due to limited airway access during the procedure, the technique was escalated to general anesthesia. Induction utilized dose-adjusted fentanyl (75 mcg), propofol (100 mg), and atracurium (30 mg) to ensure renal-independent metabolism. The surgery proceeded with stable hemodynamics. A